Impact of COVID-19 on the awareness and interest in infectious disease specialization among Japanese medical students - Naruto Kamada; Hideharu Hagiya; Satoshi Kutsuna (PLoS ONE, 2025)
Background The SARS-CoV-2 pandemic has highlighted the critical deficiency of infectious disease (ID) specialists, a subspecialty that remains underrepresented among Japanese medical students. Methods This nationwide cross-sectional survey was administered between April and August 2024 via an online questionnaire distributed to medical students throughout Japan. The survey assessed awareness of and interest in ID specialization, categorizing students by academic year: lower (first- and second-year students), middle (third- and fourth-year students), and upper grades (fifth- and sixth-year students). Results Of 502 respondents, data for 492 medical students were eligible, of whom 69.7% demonstrated awareness of ID specialists, with recognition rates increasing proportionally with academic progression. Regarding career aspirations, 9.8% of respondents expressed interest in pursuing ID specialization, with the highest proportion observed among upper-grade students (19.4%). Male students (14.8%) expressed greater interest in ID specialization than female students (5.2%). The pandemic positively influenced 5.5% of students to consider ID specialization as a future career, whereas only 0.6% reported a negative impact. Conclusions These findings underscore the necessity of enhanced educational initiatives to promote ID specialization among medical students, addressing current shortages and future infectious disease preparedness.